(untitled) (Journal of the College of Basic Education, 2022)
This study dealt with the problem of the formation of side compounds as a result of the interaction of natural organic materials with chlorine used for sterilization, as these compounds, according to extensive research and studies, cause many cancerous diseases. Therefore, it was necessary to conduct an assessment of the presence of these compounds in drinking water, specifically for the city of Baghdad.